Validation of the Malay version self-efficacy questionnaire for school situations and structural relationship between demographic profiles and levels of self-efficacy among early adolescents in primary schools, Kota Bharu - Vien, Ng Vi (2017)
Introduction: Low self–efficacy is posited to underlie problematic school attendance. This study examined validity and reliability of the Malay version Self– Efficacy Questionnaire for School Situations (SEQ–SS) among school–going early adolescents from primary schools of Kota Bharu. The author also sought the structural relationship between demographic characteristics of these early adolescents and their perceived self–efficacy. Methods: Employing a cross–sectional design, students aged ten and eleven from 5 randomly selected schools were recruited with proportionate cluster sampling method. The 25–item Self–Efficacy Questionnaire for School Situations (SEQ–SS–25), was translated into Malay using forward backward translation. Validity was examined with exploratory factor analysis (EFA) in two hundred and fifteen students. The internal consistency and test–retest reliability were determined. A further two hundred and eighteen students were recruited for structural equations modelling (SEM), in which the measurement model was examined using confirmatory factor analysis (CFA), before proceeding to describe a structural model of demographic variables and perceived efficacy forschool situations. Mean and standard deviation were used to describe the scores. SPSS 22 and Mplus 7.3 were used. Results: EFA generated four theoretical factors which differed slightly from the original SEQ–SS–25. A total of 19 items of moderately high factors loadings remained, accounting for 46% of variance. Internal consistency was adequate with Cronbach’s alpha ranging between 0.643 to 0.674. ICC of 0.672 demonstrated adequate stability. The best fitting model after iterative respecification in CFA consisted of 18 items clustering into a two factors, but not all items within the second factor were related to a unifying theme. Thus, a three– factor solution comprising of “Self–efficacy in Separation Situations”, “Self– efficacy in Socially and Personally Challenging Situations” and “Self–efficacy in Situations of Disengagement from School” was accepted as the final model. Path analysis reflected significant associations between family structure and efficacy in dealing with separation and disengagement from school, as well as family socioeconomic status with one’s ability to cope with separation situations. Mean SEQ–SS scores were 68.1 for females (Standard deviation = 9.6) and 65.1 for males (Standard deviation = 10.1). Conclusion: School attendance is motivated by cognitive processes that can be self–rated using the SEQ–SS. The Malay version showed good psychometric properties among early adolescents in Kota Bharu. Emphasis should be given to significant inter–relationships between perceived self–efficacy and two demographic factors, namely socioeconomic status and family structure, when xviii deciding on psychological interventions for individuals with low perceived efficacy.